PPAT Liability For Deeds That are Null and Void Because They do Not Meet The Legal Requirements of The Agreement Based on the Civil Code - Dewi Kusmara, Fima; Neltje Saly, Jeane (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The cancellation of the PPAT deed through a court decision, not only because of the result of the PPAT error or negligence in making the deed. But the cancellation of the PPAT deed can also be caused by the mistakes or negligence of the parties who bind themselves to each other in the deed, so that the error or omission causes a lawsuit from one of the parties. In a lawsuit stating that the PPAT deed is invalid, it must be proven invalid both from the outward, formal, and material aspects. If it cannot prove it, then the deed concerned remains legally binding for the parties interested in the deed. If the deed can be proven at trial, then there is one aspect that causes the defect of the deed, so that the deed can become a deed that is degraded or a deed under hand, even become null and void. The research method used in this study is in the form of a normative juridical approach method. Specifications The research used in this study is analytical descriptive research. The types and sources of data used by the author are secondary data types, data obtained through data sources of civil law literature studies and primary legal materials, secondary legal materials, tertiary legal materials. Data collection techniques are obtained through literature studies and interviews. The method of analysis in thesis research is in the form of Qualitative Juridical.The results of research on PPAT Liability for Deeds That Are Null and Void Because They Do Not Meet the Legal Requirements of Agreements Based on the Civil Code are PPAT that violates the code of ethics by forging PPAT deeds, PPAT that violates can get civil, criminal and administrative sanctions